ANALISIS KEPUASAN NASABAH BANK BRI KANTOR CABANG SIDOARJO - Renny Yunita Sari; Bambang Budiarto; Sugeng Hariadi (Jurusan Ilmu Ekonomi Prodi Ekonomi Pembangunan Fakultas Bisnis dan Ekonomika Universitas Surabaya, 2020)
This study discusses the influence of service quality and product quality on customer satisfaction at the Bank BRI branch office in Sidoarjo. The data used in this study were obtained from the results of a questionnaire that had been distributed to customers of the BRI branch office in Sidoarjo. This quantitative research was conducted with a survey method with purposive samplin technique. The variables used in this study are independent variables that include service quality and product quality, and customer satisfaction as the dependent variable. The data analysis method used in this study is multiple linear regression analysis. The results showed that the quality of service and product quality can affected customer loyalty at the bank branch office in Sidoarjo.